Rasmussen Syndrome and Other Inflammatory Epilepsies - Varadkar, Sophia; Cross, J. Helen (Seminars in Neurology, 2015)
An underlying immune basis is emerging in an increasing number of epileptic and encephalopathic syndromes. The immunopathological mechanisms may be categorized into antibody-mediated, T-cell cytotoxicity, and microglia-induced degeneration. The immune basis in Rasmussen syndrome is thought to be T-cell mediated. Antibodies to extracellular and intracellular epitopes are implicated in limbic and other encephalitides, characterized by seizures, movement disorder, sleep disorder, obtundation, psychosis, mutism, and other psychiatric symptoms. Extracellular antibodies are directed at cell-surface-expressed neuronal or glial proteins: glutamate receptors (N-methyl-D-aspartate and α-amino-3-hydroxy-5-methyl-4-isoxazol-propionic acid), voltage-gated potassium channel complex (contactin-associated-protein 2 [CASPR2], contactin-2 and leucin-rich, glioma-inactivated 1 [LGI1]), and γ-aminobutyric acid (GABA) receptors (GABABR and GABAAR). Antibodies to intracellular antigens are less commonly seen (for example, glutamic acid decarboxylase). Diseases caused by antibodies to cell-surface-expressed antigens are better expected to respond to immune treatments than to those where the presumed mechanism is T-cell driven. Antibodies to the folate receptor FR1 are a cause of primary cerebral folate deficiency. Febrile infection-related epilepsy syndrome (FIRES) may also have an immune basis, although this is yet to be proven. For all these epilepsies, the best treatment and the long-term outcomes are not yet clear.
Keywords: Rasmussen syndrome; Rasmussen encephalitis; epilepsy; immune; antibody; encephalitis; N-methyl-D-aspartate receptor; voltage-gated potassium channel; febrile infection-related epilepsy syndrome